Mitochondrial Dysfunction and Insulin Resistance: The Contribution of Dioxin-Like Substances - Lee, Hong Kyu (Korean Diabetes Association, 2011)
Persistent organic pollutants (POPs) are known to cause mitochondrial dysfunction and this in turn is linked to insulin resistance, a key biochemical abnormality underlying the metabolic syndrome. To establish the cause and effect relationship between exposure to POPs and the development of the metabolic syndrome, Koch's postulates were considered. Problems arising from this approach were discussed and possible solutions were suggested. In particular, the difficulty of establishing a cause and effect relationship due to the vagueness of the metabolic syndrome as a disease entity was discussed. Recently a bioassay, aryl-hydrocarbon receptor (AhR) trans-activation activity using a cell line expressing AhR-luciferase, showed that its activity is linearly related with the parameters of the metabolic syndrome in a population. This finding suggests the possible role of bioassays in the analysis of multiple pollutants of similar kinds in the pathogenesis of several closely related diseases, such as type 2 diabetes and the metabolic syndrome. Understanding the effects of POPs on mitochondrial function will be very useful in understanding the integration of various factors involved in this process, such as genes, fetal malnutrition and environmental toxins and their protectors, as mitochondria act as a unit according to the metabolic scaling law.